A lifestyle intervention programme for the prevention of Type 2 diabetes mellitus among South Asian women with gestational diabetes mellitus [LIVING study]: protocol for a randomized trial. Issue 2 (29th November 2018) - Gupta, Y.; Kapoor, D.; Josyula, L. K.; Praveen, D.; Naheed, A.; Desai, A. K.; Pathmeswaran, A.; de Silva, H. A.; Lombard, C. B.; Shamsul Alam, D.; Prabhakaran, D.; Teede, H. J.; et al.
Abstract: Aim: This study aims to determine whether a resource‐ and culturally appropriate lifestyle intervention programme in South Asian countries, provided to women with gestational diabetes (GDM) after childbirth, will reduce the incidence of worsening of glycaemic status in a manner that is affordable, acceptable and scalable. Methods: Women with GDM (diagnosed by oral glucose tolerance test using the International Association of the Diabetes and Pregnancy Study Groups criteria) will be recruited from 16 hospitals in India, Sri Lanka and Bangladesh. Participants will undergo a repeat oral glucose tolerance test at 6 ± 3 months postpartum and those without Type 2 diabetes, a total sample size of 1414, will be randomly allocated to the intervention or usual care. The intervention will consist of four group sessions, 84 SMS or voice messages and review phone calls over the first year. Participants requiring intensification of the intervention will receive two additional individual sessions over the latter half of the first year. Median follow‐up will be 2 years. The primary outcome is the proportion of women with a change in glycaemic category, using the American Diabetes Association criteria: (i) normal glucose tolerance to impaired fasting glucose, or impaired glucose tolerance, or Type 2 diabetes; or (ii) impaired fasting glucose or impaired glucose tolerance to Type 2 diabetes. Process evaluation will explore barriers and facilitators of implementation of the intervention in each local context, while trial‐based and modelled economic evaluations will assess cost‐effectiveness. Discussion: The study will generate important new evidence about a potential strategy to address the long‐term sequelae of GDM, a major and growing problem among women in South Asia. (Clinical Trials Registry of India No: CTRI/2017/06/008744; Sri Lanka Clinical Trials Registry No: SLCTR/2017/001; and ClinicalTrials.gov Identifier No: NCT03305939)